A head full of stories - Swallow, Su; Archbold, Tim (London : Zero to ten limited, 2010)
Jack's head is full- full of stories. He can't listen to another one. Then Mum has a great idea - let them all out ! Now, who will listen to the stories jack has to tell?
Location: 3C
Keywords: Short Stories